Musik Sebagai Alat Diplomasi Korea Selatan Dengan Korea Utara Tahun 2015-2020 (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This study aims to explain and describe how music has become a tool of South Korea's diplomacy with North Korea in 2015 to 2020. South Korea often uses its music, especially KPop, as a diplomatic tool to other countries. Likewise in diplomacy with North Korea, the South Korean government uses its music in various types. For example, music playback at the DMZ, joint concerts with North Korea, and annual concerts held. To see music diplomacy activities that are often associated with soft power, the author uses soft power currencies to try to explain whether the activities carried out by the South Korean government it is a soft power or not. The results found were that two of the activities discussed can be considered as soft power, namely joint concerts and regular concerts. Meanwhile, music playback in the DMZ area is not considered soft power. Keyword: South Korea, North Korea, Music Diplomacy, Soft Power Currencies